2015
DOI: 10.1017/cem.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family Medicine Resident Physicians on Emergency Department Wait Times and Patients Leaving Without Being Seen

Abstract: Objective: To quantify the effect of family medicine resident physicians on emergency department (ED) wait times and patients leaving without being seen or treated. Methods: In a medium-volume community ED over twelve months, we used retrospective chart review to compare wait times between patients seen during shifts where staff were working alone versus with a resident. We measured the time from initial triage time to physician initial assessment (T 1 ) and disposition time (LOS), and number of patients leavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One explanation for this finding is the theory of constraints, by which systems are often limited by a single bottleneck that determines overall efficiency . As has been stated by others, the bottleneck in an academic clinic is the physician, who must examine or review every patient before the appointment is over. If trainees affect the speed of the physician’s examination because of educational activities or if trainees delay the time at which the physician can examine the patient, their presence will affect the system as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this finding is the theory of constraints, by which systems are often limited by a single bottleneck that determines overall efficiency . As has been stated by others, the bottleneck in an academic clinic is the physician, who must examine or review every patient before the appointment is over. If trainees affect the speed of the physician’s examination because of educational activities or if trainees delay the time at which the physician can examine the patient, their presence will affect the system as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…[50] Wang and Vikram's research has shown that presence of a family medicine resident physician in ED is associated with reduced waiting time and patients leaving without being seen. [64] Hence, the team triage strategy through the participation of a physician as the leader could be one of the benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Few studies, however, have investigated caregiver factors and none that we are aware of have investigated the association between ED-LOS and physician specialty. [18,19] In Israel and many other countries where EM is still a relatively new specialty, there are insufficient residents and attending physicians to independently staff the ED 24 hours a day. [20] Thus, many EDs internationally are staffed by multidisciplinary teams consisting of EM physicians, internists and general surgeons along with a number of others staff roles.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies, however, have investigated caregiver factors and none that we are aware of have investigated the association between ED-LOS and physician specialty [18,19] . In Israel and many other countries where EM is still a relatively new specialty, there are insufficient residents and attending physicians to independently staff the ED 24 hours a day [20] .…”
Section: Introductionmentioning
confidence: 99%